Preparation and Characterization of the Silk Fibroin 3D Scaffolds with Porous and Interconnected Structure (Journal of Fiber Bioengineering and Informatics, 2019)
Silk fibroin (SF) is wildly used in the field of biomedical science. Considering the contradiction betweensuitable pore size and outstanding mechanical properties, this research focused on the topic of preparingthe 3D scaffolds with large pore sizes and high interconnectivity. For preparing the silk fibroin 3D scaffoldsamples, three kinds of porogens were applied in two methods which paraffin spheres were used in freezedrying. Sodium chloride (NaCl) and sodium carbonate (Na2CO3) were used in leaching respectively.Different pore size of porogens were used to control the pore size and porosities of prepared scaffoldsamples. Some basic properties of scaffold samples were characterized including surface morphology,chemical structure, porosity and mechanical performance. The best porosity of sample reached to 93%in the research.